Whale rover moving along the surface of sperm whale. (16th February 2019) - Tsuchiya, Kosuke; Tsumaki, Yuichi; Mori, Kyoichi; Okamoto, Ryosuke
ABSTRACT: Biologging, which uses small data loggers directly attached to the bodies of animals to collect various behavioral data, can be an effective means for revealing the mysteries of animal life. With respect to marine animals, zoologists have attempted to obtain video data of a sperm whale eating a giant squid using biologging. These previous efforts have been unsuccessful because the biologger, which was attached to the whale's back that emerged from the sea as the whale swam, provided poor visibility of the whale's mouth area in the deep sea. To solve this problem, we proposed a novel roving biologger or whale rover that travels along a sperm whale's body surface from its back to its mouth area using robotic technology. Four prior whale rover prototypes have been designed and developed. In this study, we further improved the whale rover design to allow for adapted travel on curved or uneven surfaces. The feasibility of this fifth prototype was confirmed using both field and laboratory experiments. These experimental results demonstrated the whale rover's ability to successfully travel across a flat surface at a depth of almost 500 m and across a curved surface in a laboratory water tank. GRAPHICAL ABSTRACT: